Analysis and modelling of non-Fickian diffusion behaviour for antimicrobial agent in composite protein films. (19th December 2016) - Lei, Q.; Bao, J. Q.; Pan, J. Z.; Zhang, Y. T.
Abstract : The migration mechanism of potassium sorbate release from Gelatin–NaCas and WPI–NaCas antimicrobial films to the food simulant system was investigated. The diffusion coefficients and migration types were determined, which contributed to the creation of a highly nonlinear model for hydrophilic composite films. It was observed that non-Fickian diffusion represented the diffusion process in the film–food simulant system, which was dependent upon matrix relaxation kinetics. The negative exponential regression model was found to excellently describe both the diffusion behaviour of potassium sorbate and the swelling phenomenon of matrix. In addition, it is advantageous in regard to the diffusion range and the sustained release compared to the well-known power law model. The improved linear superimposition model related to Brownian motion-swelling relaxation combined Fick's second law with a first-order kinetic type equation that could satisfactorily explain the relaxation behaviour to a varying degree in the diffusion of hydrophilic films quantitatively.